BS EN ISO 16148 AMD1. Gas cylinders. Refillable seamless steel gas cylinders and tubes. Acoustic emission examination (AT) and follow-up ultrasonic examination (UT) for periodic inspection and testing. (13th January 2020) - British Standards Institution,
No abstract available